Benefits of Digital Transformation and Implementation Proposition in the Defense Industry: A Literature Review - Frendiana, Mz Lerry; Soediantono, Dwi (IJOSMAS, 2022)
- The purpose of this article is to explore the benefits of digital transformation in various industries and provide recommendations to be applied to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 24 international journal articles published from 2015 to 2021 regarding the application of digital transformation in various industrial sectors and the defense industry. The analysis used uses 25 content analysis of journal articles, then coding is carried out on the contents of the reviewed journals. The results of the literature review analysis state that the application of digital transformation can increase employee productivity, speed up work processes, costs incurred by companies for labor can also be lower. low, easier to understand can make work more productive, can trigger motivation and increase performance, because it is very helpful and facilitates activities in agencies/organizations. Therefore, of course, it must also be understood that digital transformation is important and has benefits for agencies / organizations, including the existence of various activity restriction policies, such as shift distribution and work from home (WFH) policies for some agencies/organizations. Digital transformation will be very necessary, especially for communicating, coordinating and collaborating between team members in an effort to achieve the work targets that have been determined, yes of course because everything is digital, activities can be done anytime and anywhere. Based on the literature review, digital transformation is recommended to be applied to the defense industry. Based on the literature review, digital transformation is recommended to be applied to the defense industry.